Homens sobreviventes ao câncer de próstata: estudo de caso etnográfico - Pinto, Bruna Knob (2012)
This research had the aim of understanding the resilience construction of the man in illness process and survival to prostate cancer, by the context knowledge of the man in this process, and a further learning about the promotion factors of high degree of resilience of the prostate cancer survivor men. It talks about a study of an ethnographic case done with two prostate cancer survivor men with high degree of resilience. These subjects were caught from the data bank at the quantitative step of the Resilience as a survival strategy to cancer research, coordinated by Prof. Dr. Rosani Manfrin Muniz. The ethnographic data collection has followed the steps proposed by Hammersley and Atkinson (2007) for ethnographic studies, being done on the informant places, between April and May of 2012, through an interview in deepness semi-structured of the participant observation and notes registered in a dairy field and eco-map construction. The data analysis was developed based on the Minayo (2007) proposal, and interpreted through the Geertz (1989,1997) culture referential. This study results have showed that the illness and survival process was lived in different ways by each man, in spite of the equality generated by prostate cancer on the perspective of belonging to the male gender. The feelings attributed by the subjects to the cancer diagnosis and treatment were different, since one had the cancer late discovered, requiring a more invasive treatment, and the other had an early diagnosis what avoided such traumatic experience. The treatments side effects were related to sexuality and pervaded the identity of being elder. These men relationship with family, religiousness and/ or spirituality and the relationship with the health services, specially the doctor-patient, were identified as resilience promoter factors. For both, their children had a highlighted role on the process, being the paternity considered as a fundamental factor for the identity affirmation as man. The belief of a superior being was mentioned by both of them but lived in a distinct way. The men reported a good relationship with the health services, considering them as fundamental to cancer transposition. Both men in this study said were survivals and referred to themselves as privileged and lucky men. The survival was viewed by one of them as the capacity of being able to do pleasure activities. For the other, discovering cancer early and having a prestigious professional help made him not a survival but a privileged man. Highlighting the importance that, in treating and taking care of the individuals health, professionals must pay attention to cultural aspects that make that person unique and special, thus, the chances of adhesion and following therapy become higher, since he feels as an integrant part of the whole cure and overcoming process, becoming active in front of his own health.